Financing constraints, employment, and labor compensation: evidence from the subprime mortgage crisis - Alexander Popov; Jörg Rocholl (European Central Bank (ECB), 2015)
This paper identifies the effect of financing constraints on firms' labor demand. We exploit exogenous funding shocks to German savings banks during the US mortgage crisis that are unrelated to local conditions. We find that firms with credit relationships with affected banks experienced a significant decline in employment and in labor compensation relative to firms whose credit relationships were with healthy banks. We also find that the employment effect increases, and the wage effect decreases with firm size. The decline in employment at firms attached to affected banks appears to be more long-lasting than the decline in labor compensation.
Keywords: D92; G01; G21; J23; J31; 330; Credit constraints; employment; financial crisis; labor compensation